Pengaruh Penyuluhan Agama terhadap Gaya Hidup Beragama Penonton Channel Youtube Lampu Islam - Lissawa, Fatia Zahra; Solihin, Muhtar Mochamad (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2024)
Abstract: Religious counseling currently has a greater opportunity to be able to change people's behavior patterns through the use of Youtube social media by religious instructors and as a source of religious information. APJII data (2022) shows that Youtube social media (63.2%) as a popular and familiar audiovisual media that is most often accessed by Indonesians. The Lampu Islam Youtube channel is a religious study Youtube channel that takes advantage of this opportunity. This study aims; (1) to describe the level of religious lifestyle of the Youtube channel audience of Lampu Islam, (2) to analyze the effect of Religious Counseling on the Religious Lifestyle of the Youtube channel audience of Lampu Islam, (3) to analyze the significance of the influence caused by Religious Counseling on the Religious Lifestyle of the Youtube channel audience of Lampu Islam. Religious Lifestyle includes activities, interests, and opinions of a person in his religious life. This research uses a quantitative approach with a survey method. The number of samples of this study were 100 respondents. The data analysis carried out is descriptive analysis, classical assumption test, multiple linear regression test, correlation and determination coefficient test, F test (model feasibility) and T test (partial). The results of this study indicate (1) the level of religious lifestyle of the Islamic Lights YouTube channel audience is high with a percentage of 93 percent and a significance value of 0.000 <0.05, (2) there is a positive and significant influence between religious counseling on the religious lifestyle of the Islamic Lights YouTube channel audience, which means that the higher the religious counseling, the positive level of religious lifestyle in respondents will also increase, (3) the significance of the influence of religious counseling on religious lifestyle is 59.7 percent, the remaining 40.3 percent is influenced by other factors outside this study.Abstrak: Penyuluhan agama saat ini memiliki peluang yang lebih besar untuk dapat mengubah pola perilaku masyarakat melalui pemanfaatan media sosial Youtube oleh Penyuluh Agama dan sebagai sumber informasi keagamaan. Data APJII (2022) menunjukkan bahwa media sosial Youtube (63,2%) sebagai media audiovisual populer dan familiar yang paling sering diakses masyarakat Indonesia. Channel Youtube Lampu Islam merupakan saluran Youtube kajian keagamaan yang memanfaatkan peluang tersebut. Penelitian ini bertujuan; (1) mendeskripsikan tingkat gaya hidup beragama penonton channel Youtube Lampu Islam, (2) menganalisis pengaruh Penyuluhan Agama terhadap Gaya Hidup Beragama penonton channel Youtube Lampu Islam, (3) menganalisis signifikansi pengaruh yang disebabkan oleh Penyuluhan Agama terhadap Gaya Hidup Beragama penonton channel Youtube Lampu Islam. Adapum Gaya Hidup Beragama yaitu mencakup aktivitas, minat, dan opini seseorang dalam kehidupan beragamanya. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Jumlah sampel penelitian ini sebanyak 100 responden. Analisis data yang dilakukan adalah analisis deskriptif, uji asumsi klasik, uji regresi linear berganda, uji koefisien korelasi dan determinasi, uji F (kelayakan model) dan uji T (parsial). Hasil penelitian ini menunjukkan (1) tingkat gaya hidup beragama penonton channel Youtube Lampu Islam tergolong tinggi dengan persentase sebesar 93 persen dan nilai signifikansi sebesar 0,000<0,05, (2) terdapat pengaruh yang positif dan signifikan antara penyuluhan agama terhadap gaya hidup beragama penonton channel YouTube Lampu Islam yang artinya semakin tinggi penyuluhan agama maka tingkat positif gaya hidup beragama pada responden akan semakin meningkat pula, (3) signifikansi pengaruh penyuluhan agama terhadap gaya hidup beragama sebesar 59,7 persen, sisanya sebesar 40,3 persen dipengaruhi oleh faktor lain diluar penelitian ini.